Peruvian population’s genetic differences detected by both mtDNA and MBL nuclear gene haplotypical frequencies - Córdova, Jesús H. H. (2011)
Objectives: To advance in the knowledge of Peruvian populations’ origin in a phylogeographical context. Design: Population genetics study. Setting: Human Genetics Laboratory, Biological Sciences Faculty, Universidad Nacional Mayor de San Marcos, and Genetics and Molecular Biology Institute, Faculty of Medicine, Universidad San Martin de Porras, Lima, Peru. Participants: Seven Peruvian populations. Methods: Comparative analysis of mtDNA and MBL nuclear gene study results in seven Peruvian populations processed separately and then combined using PHYLYP 3.65 Program in order to obtain FST values of genetic differentiation; construction of distance trees by applying UPGMA algorithm and subsequent generated clusters’ analysis. Main outcome measures: Genetic trees. Results: Trees generated for each genetic marker had proper and distinct topologies among them. Combined processing resulted in a tree with higher values of genetic differentiation in Lago Titicaca Islands (Puno, Peru) Taquile, Amantani y Anapia, graded as very high because they showed 0.3113, 0.2949 y 0.3348 FST values with respect to the populations studied outside of Puno Department -like Chachapoyas, Pucallpa and Chiclayo-, as well as those of both Uro’s in same Puno and Lago Titicaca’s populations (0.2837). Out of Puno, the pair Chachapoyas-Pucallpa population was the least divergent with 0.0108 FST value between them, classifying as small. Conclusions: The tree obtained from markers by a combined matrix process determined that populations inhabiting in Taquile, Amantani y Anapia islands possess notable genetic divergence respect to the four remainders studied in Peru, including the Uro’s population geographically very close to them and within the same Lago Titicaca. Our next objective will be to explain these findings initially by increasing genetic markers and number of populations analyzed in Peru.